Nesting Ecology of European Hedgehogs (Erinaceus europaeus) in Urban Areas in Southeast Spain: Nest Habitat Use and Characteristics - Jana Marco-Tresserras; Germán M. López-Iborra (Animals, 2023)
Appropriate nesting sites are needed for the presence of European hedgehogs (Erinaceus europaeus) in an area, along with food availability. However, little attention has been paid to them in the literature. This study aimed at analysing, for the first time, the environmental characteristics of nesting sites chosen by hedgehogs, their spatial distribution and the effect of sex and season on them in two types of urban parks in southeastern Spain. A total of 31 hedgehogs were equipped with GPS devices, and 130 hedgehog nests were located and described. Both sexes had a similar number of nests; however, the spatial distribution of the male nests was larger, and they changed nests more frequently than females. The environment around the nests and hosting structures used also differed between the sexes, with males using a higher variety of nesting structures available and females being more selective. The differences in topography and habitat composition of the two urban parks also affected hedgehog nesting ecology, especially in reference to artificial elements like cat feeders. Further studies of nest locations at a microhabitat level are needed to contribute to a better understanding of a hedgehog’s requirements, fostering the design of more effective conservation strategies.